2015
DOI: 10.1371/journal.pone.0140645
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen-Mediated Oxidation during UVA Radiation Alters the Dynamic of Genomic DNA Replication

Abstract: UVA radiation (320–400 nm) is a major environmental agent that can exert its deleterious action on living organisms through absorption of the UVA photons by endogenous or exogenous photosensitizers. This leads to the production of reactive oxygen species (ROS), such as singlet oxygen (1O2) and hydrogen peroxide (H2O2), which in turn can modify reversibly or irreversibly biomolecules, such as lipids, proteins and nucleic acids. We have previously reported that UVA-induced ROS strongly inhibit DNA replication in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 85 publications
(117 reference statements)
0
23
0
2
Order By: Relevance
“…NAC is especially useful for increasing cell antioxidant capacity through the production of glutathione, thereby protecting the organism against reactive species (81,82) and dark CDPs (21). Actually, the use of NAC in UVA-irradiated cell cultures results in replication fork stalled rescue in ATM, ATR and homologous recombination-defective cells (47,53,83), as well as DNA protection against fragmentation (81,84). The observations of this work clearly indicate that the UVA-induced redox process damages human cells, especially XP-V, and in ATR/Chk1 pathway activation, since the use of NAC significantly decreased cell sensitivity and DNA damage, and consequently genotoxic stress (cH2AX signal), as well as Chk1 phosphorylation in UVA-irradiated XP-V cells, even in the presence of an ATR inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…NAC is especially useful for increasing cell antioxidant capacity through the production of glutathione, thereby protecting the organism against reactive species (81,82) and dark CDPs (21). Actually, the use of NAC in UVA-irradiated cell cultures results in replication fork stalled rescue in ATM, ATR and homologous recombination-defective cells (47,53,83), as well as DNA protection against fragmentation (81,84). The observations of this work clearly indicate that the UVA-induced redox process damages human cells, especially XP-V, and in ATR/Chk1 pathway activation, since the use of NAC significantly decreased cell sensitivity and DNA damage, and consequently genotoxic stress (cH2AX signal), as well as Chk1 phosphorylation in UVA-irradiated XP-V cells, even in the presence of an ATR inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Confirming these observations, studies from our lab showed that protein oxidation by UVA irradiation also affects the ability of human cells to replicate their genetic material, probably due to translesion synthesis (TLS) and NER being affected in irradiated XP-V cells (Moreno et al, 2019ab). Curiously, previous work reported that UVAinduced singlet oxygen leads to DNA replication arrest independently of cell cycle checkpoints activation, probably due to a transient decrease of dNTP pool, probably not related to the oxidation of DNA repair proteins (Graindorge et al, 2015). This suggests that UVA light-induced oxidative stress has a greater contribution in impairing proteins that participate in DNA repair and replication pathways than in inducing direct damage to DNA.…”
Section: Dna Glycosylase Neil1 Binds and Excises Psoraleninduced Monomentioning
confidence: 97%
“…During this study, cells from passage 6 to 15 were cultured in Bcomplete^DMEM, namely DMEM high glucose (Lonza or Gibco) supplemented with penicillin and streptomycin (100 U ml −1 ), 10% fetal bovine serum, and 2 mM glutamine at 37°C. As indicated in the text, we also used the MRC5Vi cell line that are immortalized human fibroblasts and cultured as previously described (Graindorge et al, 2015). For cell viability experiments, cells were at 40-50% confluent on the day of the treatments, while for all other experiments, the treatments were performed when cells were 80-90% confluent and in serum-free, phenol red-free, and glutamine-free DMEM medium in which stock solutions of the different chemicals were diluted.…”
Section: Cell Cultures Treatments and Cell Viability Assaymentioning
confidence: 99%